Economic Analysis of Law in Countering Corporate Crimes - Antoni Surbakti, Feri; Mulyati, Nani (Journal of Law, Politic and Humanities, 2024)
The existence of law in the midst of society is needed to regulate people's lives in realizing order and tranquility. The formulation of the problem in this writing is how to apply economic analysis of law in overcoming corporate crimes. The method used in this writing is normative juridical research, using conceptual approach techniques, legislative approach and historical approach. The nature of this research is descriptive and the data used in this writing is secondary data with data collection techniques carried out through literature studies and document studies. The data analysis in this writing will be analyzed qualitatively. The result and discussion in this writing is that the law in achieving its goals is not only based on justice, certainty and utility, but also seen from efficiency, value and benefit. Efficiency from an economic perspective determines the parameters of whether a law is effective or not. Law and economics are closely related, both complement each other and complement each other in regulating human behavior. Law enforcement policies in various countries have placed criminal law as an instrument to create social order and community welfare, so law enforcement against crimes committed by corporations should be carried out with an economic analysis of law approach. Law enforcement in the perspective of economic analysis of law does not only mean the prevention of corporate crime as a handling of legal cases, but what is more important to pay attention to is the impact of law enforcement on the economy, society and state interests. Countermeasures against criminal acts committed by corporations using criminal law means must be based on efficiency by paying attention to costs and benefits and carried out proportionally.